Lower extremity biomechanics and muscle activity differ between 'new' and 'dead' pointe shoes in professional ballet dancers. Issue 4 (19th May 2021) - Aquino, Jessica; Amasay, Tal; Shapiro, Sue; Kuo, Yi-Tzu; Ambegaonkar, Jatin P.
ABSTRACT: The purpose of this study was to compare lower extremity (LE) biomechanics and muscle activity between 'new' and 'dead' pointe shoes in professional female ballet dancers performing relevé and arabesque. We compared sway area, peak ankle moments, and tibialis anterior and medial gastrocnemius muscle activation amplitudes. Nine ballet dancers participated (age = 22.2 ± 2.2 years, height = 163.2 ± 6.3 cm, body mass = 50.8 ± 6.5 kg) executed three trials of relevé and arabesque on pointe shoes under two conditions: 'dead' (108–144 training hours) and 'new' (3–36 training hours). While wearing 'dead' pointe shoes, dancers had significantly higher sway area during both relevé and arabesque ( p = 0.017 and 0.028, respectively). Dancers exhibit significantly higher tibialis anterior activation (root mean square, %maximum voluntary contraction) during arabesque while wearing 'dead' pointe shoes ( p = 0.043). No significant differences were identified in other dependent variables. The increased sway area and tibialis anterior muscle activity when wearing 'dead' pointe shoes during relevé and arabesque movements demonstrates that using 'dead' shoes is more demanding. Our findings provide quantitative evidence of possible deleterious biomechanical changes when wearing dead pointe shoes that may increase LE injury risk in dancers.